Nanoconfinement promotes CO2 electroreduction to methanol on a molecular catalyst - Guoshuai Shi; Wendi Zhang; Yikun Kang; Jin Zhao; Tingyu Lu; Chunlei Yang; Mingwei Chang; Yuluo Shen; Xinyang Gao; Jing Wu; Ye-Fei Li; Kecheng Cao; et al. (Nature Communications)
Abstract Confining catalysis within a nanospace can effectively regulate intermediate configurations and product distributions. Here, we demonstrate the inner cavity of carbon nanotubes (CNTs) as a nanoreactor to promote the electrochemical conversion of CO2 to methanol (CH3OH). Cobalt phthalocyanine (CoPc) molecules are rationally incorporated into CNTs of varying diameters, exhibiting different CH3OH selectivities. CoPc confined within the CNTs is more prone to CH3OH production, whereas CoPc located on the exterior primarily facilitates CO formation. Operando spectroelectrochemical measurements and theoretical calculations demonstrate that the nanoconfined environment effectively accumulates CO as an intermediate, introduces structural deformation in CoPc molecules, enhances *CO adsorption on Co sites, and consequently improves CH3OH production. This work underscores the significance of local microenvironment in electrocatalysis and presents an approach to enhancing deep-reduction product selectivity in molecular catalysts through nanoconfinement.